Deficiencies In Teaching and Learning English As a Foreign Language In the Secondary Schools In India: Challenges in English Language Education in Indian Secondary Schools (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The process of teaching and learning English in India is notsatisfactory. Most of the Indian students, who have passed seven years oflearning English (from junior to secondary school), fail to acquire expectedlevel of proficiency in English. In the Indian context, a high percentage ofschool dropouts who were taught English for about six periods per week forseven years, leave their schools as ignorant of English usage.